Hoax and Fake News by Saracen Syndicate and the Problems for National Cyber Security - Wibowo, Andre Tri (Indonesian Journal of Counter Terrorism and National Security, 2022)
Along with the times, information technology has taken an important role in society. Information technology not only has a positive impact but also has a negative impact, this is what then gives rise to an idiom that we often hear together, that information technology is like a double-edged knife. On the one hand, with the existence of information technology, it encourages demand for products. the technology itself, such as computers, modems, facilities to build internet networks and so on, then facilitates business transactions, especially financial businesses in addition to other businesses. But on the other hand, the use of information technology also invites crime. Cybercrime is a form of virtual crime by utilizing computer media that is connected to the internet and includes everything related to criminal acts.